Composition of piezoelectric material, method for fabricating the same, piezoelectric device, and apparatus comprising piezoelectric device
Patent Information
- Application Number
- KR1020220000010
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-01-01
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2042-01-01
Smart Images

Figure 112022000001492-PAT00004_ABST
Abstract
Description
Technology Field
[0001] The present specification relates to a piezoelectric material composition, a method for manufacturing the same, a piezoelectric element, and a display device comprising a piezoelectric element. Background Technology
[0002] Piezoelectric materials are widely used as materials for ultrasonic vibrators, electromechanical transducers, and actuator components in a wide range of fields, including ultrasonic devices, imaging devices, audio devices, communication devices, and sensors.
[0003] Pb(Zr,Ti)O3 (hereinafter; PZT) series materials are utilized as the primary materials for most piezoelectric components due to their high piezoelectric properties. However, lead (Pb) is a highly toxic substance, and its high volatility during the sintering process causes serious environmental pollution.
[0004] Therefore, due to environmental pollution issues, there is a demand for the development of lead-free (Pb-free) piezoelectric materials for PZT piezoelectric materials, which account for the majority of piezoelectric materials, along with a requirement for high piezoelectric properties. The problem to be solved
[0005] The problem to be solved according to the embodiments of the present specification is to provide a piezoelectric material composition having high voltage properties without containing lead.
[0006] The problem to be solved according to the embodiments of this specification is to provide a method for manufacturing a piezoelectric material composition that can improve piezoelectric properties by orienting crystals using a template in order to provide a piezoelectric material composition having high voltage properties. The problem to be solved according to the embodiments of this specification is to provide a piezoelectric element having high voltage properties and a display device including the same.
[0007] The present specification provides a piezoelectric element having various combinations of compositions for developing a material in which a ROT structure with a high RO ratio coexists at room temperature, and provides a piezoelectric element capable of realizing the performance of a high-performance material through the process of the present specification.
[0008] The problems to be solved according to the embodiments of this specification are not limited to those mentioned above, and other unmentioned problems will be clearly understood by those skilled in the art from the description below. means of solving the problem
[0009] The piezoelectric material composition according to the embodiments of this specification is 0.96 (Na a K 1-a )(Nb b Sb 1-b )O3- (0.04-x)MZrO3- x(Bi c Ag 1-c )ZrO3(M= Sr, Ba, Ca) (where a is 0.4 ≤ a ≤ 0.6, b is 0.90 ≤ b ≤ 0.98, c is 0.4 ≤ c ≤ 0.6, and x is 0 ≤ x ≤ 0.04) is represented.
[0010] A method for manufacturing a piezoelectric material composition according to an embodiment of the present specification comprises the steps of weighing a matrix material and a seed material, mixing the matrix material and the seed material to prepare a slurry, molding the slurry to prepare a molded body, and sintering the molded body to prepare a sintered body, wherein the weighed matrix material and seed material are 0.96 (Na a K 1-a )(Nb b Sb 1-b )O3- (0.04-x)MZrO3- x(Bi c Ag 1-c )ZrO3(M= Sr, Ba, Ca) (where a is 0.4 ≤ a ≤ 0.6, b is 0.90 ≤ b ≤ 0.98, c is 0.4 ≤ c ≤ 0.6, and x is 0 ≤ x ≤ 0.04) is represented.
[0011] A piezoelectric element according to an embodiment of the present specification comprises a piezoelectric element layer including a first material layer and a second material layer surrounded by the first material layer, a first electrode portion disposed on a first surface of the piezoelectric element layer, and a second electrode portion disposed on a second surface opposite to the first surface, wherein the piezoelectric element layer is 0.96 (Na a K 1-a )(Nb b Sb 1-b )O3- (0.04-x)MZrO3- x(Bi c Ag 1-c )ZrO3(M= Sr, Ba, Ca) satisfies the composition of (where a is 0.4 ≤ a ≤ 0.6, b is 0.90 ≤ b ≤ 0.98, c is 0.4 ≤ c ≤ 0.6, and x is 0 ≤ x ≤ 0.04).
[0012] A display device according to an embodiment of the present specification includes a display panel for displaying a screen, and a piezoelectric element layer disposed on the rear surface of the display panel and comprising a first material layer and a second material layer surrounded by the first material layer, a first electrode portion disposed on a first surface of the piezoelectric element layer, and a second electrode portion disposed on a second surface facing the first surface.
[0013] Specific details according to various examples of this specification, other than the means for solving the problem mentioned above, are included in the description and drawings below. Effects of the invention
[0014] According to the embodiments of the present specification, since the piezoelectric material composition has high piezoelectric properties without containing lead, the piezoelectric element and display device including it are driven by a low driving voltage, thereby having the effect of improving piezoelectric properties.
[0015] Furthermore, according to the embodiments of the present specification, the method for manufacturing a piezoelectric material composition has the effect of significantly reducing time and cost compared to a single crystal manufacturing method, thereby greatly improving productivity.
[0016] The effects of this specification are not limited to those mentioned above, and other unmentioned effects will be clearly understood by those skilled in the art from the description below. Brief explanation of the drawing
[0017] FIG. 1 is a flowchart of a method for manufacturing a piezoelectric material composition according to an embodiment of the present specification. FIG. 2 is a cross-sectional view showing a piezoelectric material according to an embodiment of the present specification. FIG. 3 shows the crystal structure of a piezoelectric material according to an embodiment of the present specification. FIGS. 4a, FIGS. 4b, and FIGS. 4c are drawings illustrating the crystallographic orientations of the tetragonal (T), orthorhombic (O), and rhombohedral (R) of a piezoelectric material composition according to an embodiment of the present specification. Figure 5 illustrates the phase transition temperature according to the temperature change of the piezoelectric element. Figures 6a and 6b illustrate the piezoelectric performance according to the domain size. FIG. 7 shows the density and dielectric constant (ε) according to the seed content (mol%) of NaNbO3 of the piezoelectric material composition according to the embodiments of the present specification. T 33 / ε0, dielectric constant), loss factor (tanδ), piezoelectric charge constant (d 33 , Piezoelectric Charge Constant), and electromechanical coupling coefficient (k ρ This is a diagram showing the Electromechanical Coupling Factor, and Mechanical Quality Factor. Figure 8 shows the Rogering coefficient according to the seed content of the piezoelectric material composition. Figure 9 shows the phase transition temperature when 3 mol% of seed is applied to the piezoelectric material composition. FIGS. 10a to 10e are photographs of the microstructure according to the piezoelectric material composition of the present specification. FIG. 11 is a flowchart of a method for manufacturing a matrix of a piezoelectric material composition according to an embodiment of the present specification. FIG. 12 is XRD data of a matrix material according to an embodiment of the present specification. FIGS. 13a to 13e are diffraction peaks of a matrix material according to an embodiment of the present specification. FIGS. 14a to 14e are cross-sectional photographs of a matrix material according to an embodiment of the present specification. FIG. 15a shows the change in dielectric constant values according to temperature of the matrix material of the present specification, and FIG. 15b to 15f show the change in dielectric constant and loss factor according to the increase in BAZ content of the matrix material of the present specification. FIGS. 16a to 16e are graphs of temperature permittivity according to different frequencies as the BAZ content of the matrix material of the present specification increases. FIGS. 17a and FIGS. 17b are transmission electron microscope images of the matrix material of the present specification. FIG. 18 shows the relative density and permittivity (ε) of the matrix material of the present specification. T 33 / ε0, dielectric constant), piezoelectric charge constant (d 33 , Piezoelectric Charge Constant), and electromechanical coupling coefficient (k ρ This is a diagram showing the Electromechanical Coupling Factor. FIG. 19a is the piezoelectric charge constant according to the poling temperature of the matrix material, FIG. 19b is the piezoelectric charge constant according to the poling voltage, and FIG. 19c is the piezoelectric charge constant according to the annealing temperature. FIG. 20 is a flowchart of a method for manufacturing a seed of a piezoelectric material composition according to an embodiment of the present specification. Figure 21 illustrates the crystal change that occurs during the step of preparing the secondary seed. Figure 21 illustrates the crystal change that occurs during the step of preparing the secondary seed. FIG. 22 is a perspective view of a display device according to an embodiment of the present specification. FIG. 23 is a cross-sectional view taken along the cutting line I-I' of FIG. 22. FIG. 24 is a detailed drawing of the piezoelectric element of FIG. 23. Specific details for implementing the invention
[0018] The advantages and features of this specification and the methods for achieving them will become clear by referring to the embodiments described below in detail together with the accompanying drawings. However, this specification is not limited to the embodiments disclosed below but may be implemented in various different forms. These embodiments are provided merely to ensure that the disclosure of this specification is complete and to fully inform those skilled in the art of the scope of the invention, and this specification is defined only by the scope of the claims.
[0019] Shapes, sizes, ratios, angles, numbers, etc. disclosed in the drawings for explaining the embodiments of this specification are exemplary and are not limited to the depicted items. Throughout the specification, the same reference numerals refer to the same components. Furthermore, in describing this specification, if it is determined that a detailed description of related prior art could unnecessarily obscure the essence of this specification, such detailed description is omitted. Where terms such as "includes," "has," or "is made up" are used in this specification, other parts may be added unless "only" is used. Where a component is expressed in the singular, it includes cases where it is included in the plural unless specifically stated otherwise.
[0020] In interpreting the components, they are interpreted to include a margin of error even in the absence of a separate explicit statement.
[0021] In the case of describing a positional relationship, for example, when the positional relationship between two parts is described using expressions such as 'on,' 'upper,' 'lower,' or 'next to,' one or more other parts may be located between the two parts unless 'immediately' or 'directly' is used.
[0022] The terms first, second, etc. are used to describe various components, but these components are not limited by these terms. These terms are used merely to distinguish one component from another. Accordingly, the first component mentioned below may be the second component within the technical scope of this specification.
[0023] The features of each of the various embodiments of this specification may be combined or combined with one another, either partially or wholly, and may technically enable various interlocking and operation. Each embodiment may be implemented independently of one another or may be implemented together in an associated relationship.
[0024] FIG. 1 is a flowchart of a method for manufacturing a piezoelectric material composition according to an embodiment of the present specification.
[0025] Referring to FIG. 1, a method for manufacturing a piezoelectric material composition according to an embodiment of the present specification comprises the steps of weighing a base material of the piezoelectric material composition (S101), mixing the weighed base material (S102), molding the base material (S103), sintering the molded piezoelectric material composition (S104), and forming an electrode on the sintered piezoelectric material composition (S105). Conditions according to the method for manufacturing the piezoelectric material composition, such as temperature, viscosity, and time, do not limit the contents of the present specification.
[0026] First, the step of weighing the matrix material of the piezoelectric material composition (S101) is a step of weighing the materials prepared to satisfy the molar ratio of Chemical Formula 1 below through the method of preparing the matrix material (S10) and the method of preparing the seed material (S20).
[0027] A piezoelectric material composition can be prepared to satisfy the following chemical formula 1.
[0028] [Chemical Formula 1]
[0029] 0.96(Na a K 1-a )(Nb b (T 1-b ))O3- (0.04-x)MZrO3- x(Bi c Ag 1-c )ZrO3(T=Sb, Ta), (M=Sr, Ba, Ca) + d mol% NaNbO3
[0030] Here, a is 0.4 ≤ a ≤ 0.6, b is 0.90 ≤ b ≤ 0.98, c is 0.4 ≤ c ≤ 0.6, d is 0 ≤ d ≤ 5.0, and x can be 0 ≤ x ≤ 0.04.
[0031] For example, the parent material is a condition excluding the seed NaNbO3 in Chemical Formula 1, and can be prepared by the method (S10) for preparing the parent material described later in FIG. 11.
[0032] The seed material has a NaNbO3 composition and may have a size of 10 m or more, and the aspect ratio of the seed may be in the range of 5 to 20, and may be prepared by the seed manufacturing method (S20) described in FIG. 20 below.
[0033] The seed material can be added in an amount of 1 to 5 mol% with respect to the total material composition of Formula 1, and, for example, 3 mol%.
[0034] Next, the step of mixing the weighed matrix material (S102) is the step of mixing the matrix material and the seed material weighed in the previous step.
[0035] The synthesized matrix material may include the step of preparing a composed slurry and the step of mixing a seed material into the slurry containing the matrix material.
[0036] For example, the step of preparing a slurry composed of a matrix material may involve adding appropriate amounts of a dispersant and a solvent to a matrix material having the composition of Formula 1. For example, the solvent may include at least one of ethanol, methanol, isopropanol, methyl ethyl ketone (MEK), toluene, and distilled water, but is not limited thereto. By adding appropriate amounts of a dispersant and a solvent to the matrix material, a slurry in which the matrix material is well dispersed in the solvent may be prepared. According to the embodiments of this specification, the dispersant may be used to reduce the viscosity of the slurry containing the matrix material.
[0037] In addition, ball milling can be performed by adding appropriate amounts of binder and plasticizer to the previously prepared matrix material slurry. The binder can provide strength, flexibility, ductility, durability, toughness, and softness to the molded body (green tape). The binder may include at least one of polyvinyl butyral (PVB) resin, polyvinyl alcohol (PVA), and polyethylene glycol (PEG), but is not limited thereto, and any binder known in the field of piezoelectric material compositions may be used. A plasticizer may be added to provide elastic and plastic properties to the molded body. The plasticizer may include at least one series of phthalate-based plasticizers, adipate-based plasticizers, phosphate-based plasticizers, polyether-based plasticizers, and polylyester-based plasticizers, and any plasticizer material known in the field of piezoelectric material compositions may be used.
[0038] The step of mixing the seed material into the matrix material can be performed through a milling process by mixing the seed material into a slurry containing the matrix material prepared in the preceding step, and can be performed at a low speed (e.g., 40 rpm) without balls for a relatively short time compared to other mixing steps.
[0039] In addition, the method may further include a degassing step to remove bubbles and gas and an aging step after the seed material is added and mixed into a slurry containing a matrix material.
[0040] The degassing step is a step for adjusting the viscosity of the slurry to an appropriate level for the molding process in the step of molding the piezoelectric material described later. For example, the degassing step can be adjusted to have a viscosity of 1700 cPs to 2400 cPs using a vacuum stirrer at room temperature.
[0041] The aging step is a step to bring the slurry back to room temperature, as the solvent may cool down when it volatilizes during the preceding degassing step. For example, the aging step can be performed by stirring for a short time at a low speed of about 40 rpm using a stirrer.
[0042] Next, the step of molding the piezoelectric material (S103) is a step of manufacturing a molded body having a predetermined volume and shape from a slurry in which the matrix material and seed material prepared in the preceding step (S102) are mixed.
[0043] For example, the step of forming a piezoelectric material may include a tape casting step, a step of forming the tape-cast piezoelectric material first, and a step of forming the first-formed piezoelectric material second.
[0044] The tape casting step is a step of tape casting a slurry mixed with the matrix material and seed material prepared in the previous step using a tape casting device, and when tape casting with a slurry having a viscosity of 1700 to 2400 cPs, it can be cast to a thickness of about 30 m.
[0045] The step of primary forming of the tape-cast piezoelectric material can be performed by warm isostatic pressing (WIP), and the step of secondary forming of the tape-cast piezoelectric material can be performed by cold isostatic pressing (CIP), and can be used to increase the density of the sintered body in the sintering step described later. In addition, in the case of warm isostatic pressing, for the piezoelectric material composition according to the embodiments of this specification, it can be performed when a molded body is prepared based on stacking and lamination such as tape casting.
[0046] Additionally, the step of forming the piezoelectric material (S103) may further include a degreasing step after the first forming step, and the degreasing step is a step of removing solvent or organic matter. The degreasing step may be performed by maintaining the material in a furnace at a temperature range of 300°C to 600°C for approximately 40 hours and then cooling it down to room temperature.
[0047] Next, the step of sintering the molded body (S104) is described.
[0048] The sintering step can be carried out in a single temperature range followed by furnace cooling. For example, the sintering temperature is 1090 o It can be C, and the duration can be 3 hours.
[0049] Next, the step (S105) of forming an electrode on the sintered body is described.
[0050] Electrodes can be formed on the first surface and the second surface opposite the first surface of the piezoelectric material sintered body prepared in the preceding step. For example, the electrodes can be formed by applying silver (Ag), but are not limited thereto, and known conventional electrodes can be used without limitation.
[0051] FIG. 2 is a cross-sectional view showing a piezoelectric material according to an embodiment of the present specification.
[0052] Referring to FIG. 2, the piezoelectric material (10) according to an embodiment of the present specification may include a plurality of grains composed of a first material (11) and a second material (12). The grains composed of the first material (11) and the second material (12) may be separated by grain boundaries (GB).
[0053] The second material (12) can be formed inside the first material (11), and the first material (11) can grow crystal grains based on the crystal direction of the second material (12), so that a plurality of first materials (11) can have the same crystal direction, for example, the first material (11) can have a (001) crystal direction. Accordingly, the first material (11) can be arranged to surround the second material (12).
[0054] The second material (12) may be located in the central part of the first material (11). Here, the central part is not numerically exactly half of the first material (11) having a predetermined volume, but may be a predetermined region including the center of the first material (11) having a predetermined volume, and the second material (12) may be included within the scope of this specification even if it is located at a position away from the center of the first material (11). For example, the second material (12) may be positioned so as to be offset adjacent to the grain boundary (GB), which is the boundary of a plurality of first materials (11), while being placed within the first material (11) for crystal direction growth.
[0055] Additionally, the piezoelectric material (10) may further include electrode portions (13) formed on each of the first surface and the second surface opposite the first surface of the sintered body of the first material (11) and the second material (12) formed with a predetermined thickness. When the piezoelectric material (10) further includes electrode portions (13), it can function as a piezoelectric element.
[0056] The first material (11) may be a matrix material. The first material (11) may be prepared by the method (S10) for preparing the matrix material described below.
[0057] The second material (12) may be a seed material. The second material (12) may be prepared by the method (S20) for preparing a seed material described below.
[0058] The second material (12) can act as a template in the sintering step (S104) of the method (S100) for manufacturing a piezoelectric material composition according to an embodiment of the present specification, so that the first material (11) can grow along the crystal direction of the second material (12). For example, the first material (11) can grow so that the crystal direction is oriented in the same direction as it is sintered depending on the crystal direction of the second material (12).
[0059] FIG. 3 shows the crystal structure of a piezoelectric material according to an embodiment of the present specification.
[0060] Referring to FIG. 3, a piezoelectric material having the composition of Formula 1 of this specification may have a conventional ABX3 structure. Here, A is a first cation, B is a second cation, and X is an anion bonded to them. The first cation may be potassium (K), sodium (Na), strontium (Sr), bismuth (Bi), and silver (Ag); the second cation may be niobium (Nb), antimony (Sb), and zirconium (Zr); and the anion may be oxygen (O). The first cation and the anion are AX 12It may be a structure that forms a cubic octahedral structure, and the second cation may be bonded to an octahedral structure with BX6.
[0061] FIGS. 4a, FIGS. 4b, and FIGS. 4c are drawings illustrating the crystallographic orientations of the tetragonal (T), orthorhombic (O), and rhombohedral (R) of a piezoelectric material composition according to an embodiment of the present specification.
[0062] Referring to FIGS. 4a, 4b, and 4c, the piezoelectric performance of the piezoelectric ceramic according to the present specification can be increased as the number of crystallographic orientations of spontaneous polarization increases. The tetragonal structure has 6 crystallographic orientations, the orthorhombic structure has 12 crystallographic orientations, and the rhombohedral structure has 8 crystallographic orientations. To increase piezoelectric performance, compositional optimization is required in which rhombohedral (R)-orthorhombic (O)-tetragonal (T) (hereinafter ROT) crystal structures coexist.
[0063] Figure 5 shows pure (Na 0.5 K 0.5 This shows the phase transition temperature according to the temperature change of the NbO3 piezoelectric element.
[0064] Referring to Fig. 5, -100 o C ~ -50 o C to T R-O a, approximately 200 o C to T O-T It can be seen that exists. Pure (Na 0.5 K 0.5 By adding bismuth (Bi), silver (Ag), strontium (Sr), antimony (Sb), zirconium (Zr), etc. to )NbO3, a material in which the ROT structure coexists at room temperature can be produced.
[0065] Figures 6a and 6b illustrate the piezoelectric performance according to the domain size.
[0066] Referring to FIGS. 6A and 6B, as the domain size decreases, d 33The value shows an increasing trend, which indicates that as the domain size decreases, it reduces domain boundary energy and facilitates domain rotation, thereby contributing to the improvement of piezoelectric properties.
[0067] FIG. 7 shows the density and dielectric constant (ε) according to the seed content (mol%) of NaNbO3 of the piezoelectric material composition according to the embodiments of the present specification. T 33 / ε0, dielectric constant), loss factor (tanδ), piezoelectric charge constant (d 33 This is a figure showing the Piezoelectric Charge Constant, and the Electromechanical Coupling Factor (kρ). The piezoelectric material composition of Fig. 7 was prepared with a (Na,K,Sr,Bi,Ag)(Nb,Sb,Zr)O3 composition, and a NaNbO3 seed was added.
[0068] Referring to Fig. 7, it can be seen that the density exceeds 93% in the range where the seed content (mol%) of NaNbO3 is 0 to 3 mol%. For example, the seed content (mol%) of NaNbO3 showed a value of 90.1% at 3 mol%.
[0069] permittivity (ε T 33 It can be seen that / ε0, dielectric constant) exhibits a value exceeding 2000 in the range where the seed content (mol%) of NaNbO3 is 2 mol% to 5 mol%. For example, when no NaNbO3 seed was added, the dielectric constant value was approximately 1800, and when 1 mol% of NaNbO3 seed was added, the dielectric constant value was approximately 1990.
[0070] It can be seen that the loss factor (tanδ) has a value of approximately 0.033 when the seed content (mol%) of NaNbO3 is 0, and a value exceeding 0.035 in the range of 1 mol% to 5 mol% of the seed content (mol%) of NaNbO3.
[0071] Piezoelectric charge constant (d 33 The Piezoelectric Charge Constant (PC / N) showed a value of approximately 478 pC / N when the seed content (mol%) of NaNbO3 was 0, a value of approximately 538 pC / N when the seed content (mol%) of NaNbO3 was 1 mol%, and a value of 689 pC / N or higher in the range of 2 mol% to 5 mol%. For example, when the seed content (mol%) of NaNbO3 was 3 mol%, a value of 760 pC / N was observed.
[0072] It can be seen that the electromechanical coupling factor (kρ) has a value of approximately 0.476 when the seed content (mol%) of NaNbO3 is 0, and a value exceeding 0.5 in the range of 1 mol% to 5 mol% of the seed content (mol%) of NaNbO3, and, for example, a value of 0.58 when the seed content (mol%) of NaNbO3 is 3 mol%.
[0073] Figure 8 shows the Rogering coefficient according to the seed content of the piezoelectric material composition. In Figure 8, the actual composition of the piezoelectric material composition used for measurement was (Na,K,Sr,Bi,Ag)(Nb,Sb,Zr)O3.
[0074] Here, the lotgering factor (Lf(%)) can be calculated using the following mathematical formula (2).
[0075] [Mathematical Formula 1]
[0076] Here, p is the degree of orientation calculated by mathematical formula (1), and p0 is the fraction of I00l in a randomly oriented piezoelectric material composition of the same composition. The degree of orientation (p) can be calculated by the following mathematical formula (2).
[0077] [Mathematical Formula 2]
[0078]
[0079] Here, l(00l) represents diffraction peaks such as (001) and (002) expressed as (00l), and Inon-(00l) represents diffraction peaks such as (110), (111), (210), and (211) not expressed as (00l).
[0080] Referring to Fig. 8, it can be seen that if no seed is added to the piezoelectric material composition, no orientation occurs at all, and that a Rosering factor of 94.7% or higher is exhibited in the range of 1 mol% to 5 mol% of the seed content (mol%) of NaNbO3, and that the highest degree of crystal orientation is exhibited at 3 mol%.
[0081] Referring to Figures 7 and 8, it can be seen that in the range where the seed content (mol%) of NaNbO3 is 1 mol% to 5 mol%, the density, permittivity, loss factor, piezoelectric charge constant, and electromechanical coupling coefficient can be increased, and the degree of crystal orientation is increased.
[0082] Figure 9 shows the phase transition temperature when 3 mol% of seed is applied to the piezoelectric material composition. In Figure 9, the composition of the piezoelectric material used for measurement was 0.96(NaK)(NbSb) - 0.02(SrZr) - 0.02(BiAg)ZrO3.
[0083] Referring to Fig. 9, approximately 41 o A tetragonal-orthorhombic phase transition region exists near C, and approximately 151 o It can be seen that a tetragonal-cubic phase transition occurs near C.
[0084] FIGS. 10a to 10e are photographs of the microstructure according to the piezoelectric material composition of the present specification. The piezoelectric material composition used for the measurement in FIG. 10 was 0.96(NaK)(NbSb) - 0.02(SrZr) - 0.02(BiAg)ZrO3, and the photograph was taken in a direction perpendicular to the casting direction.
[0085] Figure 10a shows the case without using NaNbO3 seeds, and it can be seen that most of them exist in sizes of 20 μm or less.
[0086] Figures 10b to 10e show NaNbO3 seeds of 1 mol%, 2 mol%, 3 mol%, and 5 mol%, respectively, and it can be seen that most of the grains are larger than 25 μm.
[0087] FIG. 11 is a flowchart of a method for manufacturing a matrix material of a piezoelectric material composition according to an embodiment of the present specification.
[0088] Referring to FIG. 11, a method for manufacturing a matrix material of a piezoelectric material composition according to an embodiment of the present specification comprises the steps of: weighing a raw material having Formula 2 (S11); mixing the raw material (S12); calcining the mixed raw material to synthesize it (S13); grinding the synthesized matrix material (S14); molding the ground matrix material (S15); sintering the matrix molded body (S16); and forming an electrode on the matrix sintered body (S17). Conditions according to the method for manufacturing a piezoelectric material composition, such as temperature, pressure, and time, do not limit the contents of the present specification.
[0089] First, in the method for manufacturing a matrix material of a piezoelectric material composition according to an embodiment of the present specification, the step of weighing the raw material (S11) may be a step of weighing the matrix material according to the molar ratio and adding an appropriate amount of solvent.
[0090] The matrix material can satisfy the following chemical formula 2.
[0091] [Chemical Formula 2]
[0092] 0.96(Na a K 1-a )(Nb b (T 1-b ))O3- (0.04-x)MZrO3- x(Bi c Ag 1-c )ZrO3(T=Sb, Ta), (M=Sr, Ba, Ca)
[0093] Here, a is 0.4 ≤ a ≤ 0.6, b is 0.90 ≤ b ≤ 0.98, c is 0.4 ≤ c ≤ 0.6, and x can be 0 ≤ x ≤ 0.04.
[0094] For example, the matrix material satisfying Chemical Formula 2 may be (Na,K,Sr,Bi,Ag)(Nb,Sb,Zr)O3, and 0.5 mol% of iron oxide (Fe2O3) may be added to increase sinterability.
[0095] In the weighing step, sodium carbonate (Na2CO3), potassium carbonate (K2CO3), niobium oxide (Nb2O5), antimony oxide (Sb2O3), strontium carbonate (SrCO3), zirconium oxide (ZrO2), calcium carbonate (CaCO3), bismuth oxide (Bi2O3), silver oxide (Ag2O), and iron oxide (Fe2O3) are weighed according to the molar ratio of the composition to be synthesized, placed in a nylon jar, and an appropriate amount of solvent (e.g., ethanol) may be added.
[0096] Next, the step of mixing raw materials (S12) is a step of mixing and grinding the weighed raw materials and ethanol using a ball mill process for 24 hours. Additionally, the mixing step may further include a drying step to separate the powder mixed with the solvent after the mixing step. Here, the drying step can be performed by placing the mixed raw materials in a dish and drying them sufficiently at a temperature of 100°C.
[0097] In addition, according to an embodiment of the present specification, the step of mixing raw materials (S12) may further include a calcination step (S13) for synthesizing the first mixed raw materials.
[0098] The step of synthesizing (S13) may be a step of finely grinding the dried mixture after mixing is completed, placing it in an alumina crucible, heating it in an electric furnace at a heating rate of 5 ℃ / min, calcining it at 850℃ for 6 hours, and then naturally cooling it to room temperature.
[0099] Next, the step of grinding the synthesized matrix material (S14) may be a step of adding a solvent (ethanol) to the synthesized matrix material and grinding it for 24 hours using a ball mill process to make the particles smaller.
[0100] Additionally, the grinding step may further include a drying step to separate the powder mixed with the solvent after the grinding step. Here, the drying step can be performed by placing the ground matrix material in a dish and drying it sufficiently at a temperature of 100°C, and, for example, drying can be carried out for 3 hours.
[0101] Additionally, according to an embodiment of the present specification, the step (S14) of crushing the super-synthesized matrix material may further include a step of sieving the material.
[0102] The screening step is a step of filtering out finely ground, dried powder using a mortar and pestle with a 40-mesh sieve to produce powder composed of particles smaller than a certain size. Powder that passes through a 40-mesh sieve can have a size of 400 mm or less.
[0103] Next, the step of forming the crushed matrix material (S15) may be a step of press-molding the selected powder.
[0104] For example, the step of forming the secondary mixed material may be a step of placing it into a circular molding mold and uniaxially pressing it, and the pressure of the uniaxially pressing may be 100 kg / f, but is not limited thereto.
[0105] Next, the step of sintering the mother body (S16) may be a step of sintering at a set sintering temperature.
[0106] For example, the sintering temperature can be performed in the range of 1070 to 1110℃, and the sintering time can be maintained for 3 to 6 hours.
[0107] Next, the step of forming an electrode on the matrix sintered body (S17) may be a step of applying an electrode to one side of the sintered body and the other side opposite to the one side.
[0108] For example, the electrode applied to the sintered body may be a silver (Ag) electrode, but is not limited thereto.
[0109] In addition, the method may further include a step of poling the sintered body coated with electrodes after coating the electrodes, and the poling step may align the polarization by applying an electric field of 4 kV / mm for about 30 minutes in silicone oil set to a temperature of, for example, 0°C to 40°C.
[0110] FIG. 12 is XRD (X-ray diffraction pattern) data of a matrix material according to an embodiment of the present specification.
[0111] In Fig. 12, the X-axis represents the 2θ value of X-ray diffraction, and the vertical axis represents relative intensity.
[0112] In Fig. 12, the composition of the matrix material was prepared as 0.96(NaK)(NbSb) - (0.04-x)CaZrO3 - x(BiAg)ZrO3 and sintered at 1090℃ for 3 hours. Measurements were taken by changing x=0 in a, x=0.01 in b, x=0.02 in c, x=0.02 in d, x=0.03 in e, and x=0.04 in e.
[0113] Referring to Fig. 12, it can be seen that as the amount of BAZ added increases, a uniform perovskite structure without secondary phases is obtained throughout the entire composition.
[0114] FIGS. 13a to 13e are diffraction peaks of a matrix material according to an embodiment of the present specification. These are diffraction peaks of the matrix material at 66.5° at a low speed of 0.3° / min. FIG. 13 shows small angle X-ray results. Small angle X-rays are typically used to analyze 2θ values in the range of 1 to 1.5 degrees and to analyze nanostructures, and in the present specification, they were used to observe the coexistence of phases, phase transitions, etc., within the corresponding 2θ range.
[0115] In Fig. 13, the X-axis represents the 2θ value of X-ray diffraction, and the vertical axis represents relative intensity.
[0116] In Fig. 13, the composition of the matrix material was prepared as 0.96(NaK)(NbSb) - (0.04-x)CaZrO3 - x(BiAg)ZrO3 and sintered at 1090℃ for 3 hours. The values were measured by changing x=0 in a, x=0.01 in b, x=0.02 in c, x=0.02 in d, x=0.03 in e, and x=0.04 in e.
[0117] Referring to Fig. 13a, it can be seen that when BAZ is not added, the rhombohedral (R) phase and the orthorhombic (O) phase coexist. Referring to Figs. 13b to 13e, it can be seen that the T phase tends to increase as the amount of BAZ added increases. Additionally, referring to Fig. 13e, it can be seen that when BAZ x=0.04 is added, the orthorhombic (O) phase disappears and the structure has a coexistence of the rhombohedral (R) and tetragonal (T) phases.
[0118] FIGS. 14a to 14e are cross-sectional photographs of a matrix material according to an embodiment of the present specification.
[0119] In FIGS. 14a to 14e, the matrix material was prepared with a composition of 0.96(NaK)(NbSb) - (0.04-x)CaZrO3 - x(BiAg)ZrO3, and 0.5 mol% of iron oxide (Fe2O3) was added for sinterability.
[0120] Figure 14a is a photograph taken after polishing the fracture surface of a sample prepared with x=0, b is x=0.01, c is x=0.02, c is x=0.02, d is x=0.03, and e is x=0.04.
[0121] Referring to Fig. 14a, it can be seen that it contains two types of crystal grains: large grains of 23 µm and small grains of 0.5 µm. Referring to Figs. 14b through 14e, it is shown that as the BAZ content increases, only large-sized crystal grains are present, which implies that BAZ influences crystal growth. Furthermore, it can be seen that the piezoelectric properties increase with increasing crystal grain size through the tendency of the piezoelectric properties to increase as the crystal grain size increases.
[0122] FIG. 15a shows the change in dielectric constant values according to temperature of the matrix material of the present specification, and FIG. 15b to 15f show the change in dielectric constant and loss factor according to the increase in BAZ content of the matrix material of the present specification. In FIG. 15a to 15f, the matrix material was prepared with a composition of 0.96(Na,K)(Nb,Sb)O3-(0.04-x)CaZrO3+x(Bi,Ag)ZrO3, and 0.5 mol% of iron oxide (Fe2O3) was added for sinterability.
[0123] Referring to FIGS. 15a through 15f, the phase transition temperature T across the entire composition c It can be seen that there is no significant change with the addition of BAZ around 178 ℃, and the transition temperature (T) of the rhombohedral (R)-orthorhombic (O) system R-O) shows a nearly constant trend, and as confirmed by the diffraction pattern, the 0.96(Na,K)(Nb,Sb)O3- (0.04-x)CaZrO3 composition without BAZ addition exhibits the coexistence of rhombohedral and orthorhombic systems at room temperature. Furthermore, with increasing BAZ content, the transition temperature T of the orthorhombic (O)-tetragonal (T) system O-T As the value gradually decreases, at the composition x=0.03, the ratio of the three crystal structures is approximately 3:3:3, but at the composition x=0.04, the phase transition to the orthorhombic system is skipped, and a structure in which rhombohedral and tetragonal phases coexist is formed.
[0124] FIGS. 16a to 16e are graphs of temperature permittivity according to different frequencies as the BAZ content of the matrix material of the present specification increases. In FIGS. 16a to 16e, the matrix material was prepared with a composition of 0.96(Na,K)(Nb,Sb)O3-(0.04-x)CaZrO3-x(Bi,Ag)ZrO3, and 0.5 mol% of iron oxide (Fe2O3) was added for sinterability.
[0125] Referring to Fig. 16a, even if the frequency changes, T O-T It can be seen that the temperature of the dielectric peak is constant. Referring to Figures 16b through 16e, it can be seen that the dielectric is a relaxor dielectric having nanodomains or PNRs (Polar nano regions), or that the dielectric peak tends to vary with frequency due to defect dipoles. For example, in Figure 16b, T compared to 500 kHz at 100 Hz O-T It can be seen that the dielectric peak is shifted by approximately 1.5°C, and in Fig. 16c, T relative to 500 kHz at 100 Hz O-T It can be seen that the dielectric peak is shifted by approximately 5.5°C, and in Fig. 16d, T relative to 500 kHz at 100 Hz O-TIt can be seen that the dielectric peak is shifted by approximately 14°C, and in Fig. 16e, T at 100 Hz relative to 500 kHz O-T It can be seen that the dielectric peak is shifted by about 15°C.
[0126] Therefore, it can be seen that the matrix material according to the present specification has nanodomains by adding the composition of BAZ through having frequency dependence.
[0127] FIGS. 17a and FIGS. 17b are transmission electron microscope images of the matrix material of the present specification. In FIGS. 17a and FIGS. 17b, the matrix material was prepared with a composition of 0.96(Na,K)(Nb,Sb)O3-(0.04-x)CaZrO3-x(Bi,Ag)ZrO3, 0.5 mol% of iron oxide (Fe2O3) was added for sinterability, and FIG. 17a was taken after preparation with x=0 and FIG. 17b with x=0.03.
[0128] Referring to Figures 17a and 17b, the composition of x=0 showed a domain size of about 100 nm, and the composition of x=0.03 was confirmed to have a nanodomain structure of about 3 x 20 nm.
[0129] Combining Figures 17a and 17b and Figure 16, the phenomenon of frequency dependence in dielectric properties can be attributed to the formation of nano domains or localized nano regions (polar nano regions, PNRs).
[0130] Therefore, it can be seen that nano-sized domain structures or localized polar nano regions (PNRs) can be formed by the addition of BAZ, and that they exhibit frequency dispersion characteristics.
[0131] FIG. 18 shows the relative density and permittivity (ε) of the matrix material of the present specification. T 33 / ε0, dielectric constant), piezoelectric charge constant (d 33, Piezoelectric Charge Constant), and electromechanical coupling coefficient (k ρ This is a diagram showing the Electromechanical Coupling Factor. In Fig. 18, the matrix material was prepared with a composition of 0.96(Na,K)(Nb,Sb)O3- (0.04-x)CaZrO3- x(Bi,Ag)ZrO3 and sintered at 1090℃ for 3 hours.
[0132] Referring to Fig. 18, it can be seen that the relative density is approximately 92% or higher in the BAZ content range of 0.00 to 0.04, and that the permittivity and piezoelectric constant show a tendency to gradually increase with increasing BAZ content. It can be seen that the loss factor has a value of 4% or less in the BAZ content range of 0.00 to 0.04. The piezoelectric constant is d at composition x=0.03, which has three crystal structures—rhombohedral (R), orthorhombic (O), and tetragonal (T)—in similar proportions. 33 It exhibits the best piezoelectric properties at = 710 pC / N, and as it increases beyond this, the tetragonal (T) phase becomes more abundant, so at the composition x=0.04, d 33 It can be seen that the piezoelectric properties begin to degrade up to 565 pC / N. The electromechanical coupling factor (kρ) represents the coefficient value that converts stress transmitted to the material into electric charge, and when it is 1, it can have a conversion efficiency of 100%. It can be seen that a value of approximately 0.40 or higher is observed in the range of BAZ content from 0.00 to 0.04.
[0133] FIG. 19a shows the piezoelectric charge constant according to the poling temperature of the matrix material, FIG. 19b shows the piezoelectric charge constant according to the poling voltage, and FIG. 19c shows the piezoelectric charge constant according to the annealing temperature. In FIG. 19a to 19c, the matrix material is 0.96(NaK)(NbSb)O3-0.01CaZrO3-0.03(Bi 0.5 Ag0.5 It was prepared with a composition of ZrO3.
[0134] Referring to Fig. 19a, since the composition x=0.03 has a three-phase crystal structure of rhombohedral (R), orthorhombic (O), and tetragonal (T) at around 20°C, it can be seen that the best piezoelectric constant value is also obtained at a poling temperature of around 20°C. Referring to Fig. 19b, it can be seen that the poling voltage saturates at around 1 kV / mm. Referring to Fig. 19c, it can be seen that the piezoelectric charge constant decreases as the annealing temperature increases, and it was confirmed that it decreases slightly to a value of 568 pC / N at 130°C, and the piezoelectric properties decrease rapidly above 130°C. This is because it approaches the ferroelectric-paraelectric phase transition region starting from a temperature of 150°C or higher.
[0135] FIG. 20 is a flowchart of a method for manufacturing a seed of a piezoelectric material composition according to an embodiment of the present specification.
[0136] Referring to FIG. 20, a method for manufacturing a seed of a piezoelectric material composition according to an embodiment of the present specification includes the steps of: weighing a seed material first (S21), preparing a first seed (S22), weighing a second seed second (S23), and preparing a second seed (S24).
[0137] First, the step of weighing the seed material first (S21) is a step of weighing the first seed material according to the molar ratio and adding an appropriate amount of solvent.
[0138] Here, the molar ratio of the composition to be synthesized from the first seed is (Bi 2.5 Na 3.5 )Nb5O 16 It can be. Therefore, the first seed can be called the "BNN seed" below.
[0139] For example, in the first weighing step of the seed material, sodium carbonate (Na2CO3), niobium oxide (Nb2O5), bismuth oxide (Bi2O3), and sodium chloride (NaCl) are weighed according to the molar ratio of the composition to be synthesized and placed in a nylon jar, and an appropriate amount of solvent can be added. For example, the solvent may be ethanol, but is not limited thereto.
[0140] In addition, the ratio of sodium carbonate (Na2CO3), niobium oxide (Nb2O5), and bismuth oxide (Bi2O3) to sodium chloride (NaCl) can be adjusted during the first weighing step. For example, the ratio of oxides containing sodium carbonate (Na2CO3), niobium oxide (Nb2O5), and bismuth oxide (Bi2O3) to sodium chloride may be 1:1.5, but is not limited thereto.
[0141] The step of preparing the primary seed (S22) may further include the step of mixing the material weighed in the preceding step and the step of synthesizing the mixed primary seed material.
[0142] For example, the mixed primary seed material can be mixed with a solvent and mixed and ground using a ball mill process for 12 hours. Additionally, the step of mixing the primary seed may further include a drying step to separate the powder mixed with the solvent after the mixing and grinding step is completed. Here, the drying step can be performed by placing the primary mixed matrix material into a dish and drying it sufficiently at a temperature of 100°C.
[0143] For example, the phase synthesis step may be a step of mixing and drying the primary seed material, then finely grinding the mixture in a mortar and pestle, placing it in an alumina crucible, heating it in an electric furnace at a heating rate of 5 ℃ / min, calcining it at 1100-1175℃ for 6 hours, and then naturally cooling it to room temperature. The BNN seed after calcination may have a predetermined plate-like shape. Here, the phase synthesis step of the primary seed material may be referred to as primary calcination.
[0144] The step of preparing the primary seed (S22) may further include the step of washing the primary seed after calcination is completed.
[0145] For example, the step of washing the primary seeds may be filtered after washing 5 to 10 times with water at 80°C or higher to remove sodium chloride (NaCl) adhering to the primary seed powder.
[0146] Next, the second weighing step (S23) may be a step of adding a substance containing sodium to substitute bismuth (Bi) of the first seed powder and an appropriate amount of solvent and weighing it to match the molar ratio of the composition.
[0147] Here, the molar ratio of the composition of the secondary seed can be NaNbO3. Therefore, the secondary seed can be referred to as the "NN seed" below.
[0148] For example, in the second weighing step, sodium carbonate (Na2CO3) and sodium chloride (NaCl) are weighed according to the molar ratio of the composition to be synthesized and placed in a beaker, and an appropriate amount of solvent can be added. For example, the solvent may be ethanol, but is not limited thereto.
[0149] Next, the step of preparing the secondary seed (S24) may include the step of mixing the secondary weighed material and performing a topochemical reaction.
[0150] For example, the step of mixing the second weighed material can be performed through a stirring process, and can be performed by placing a magnetic bar into a beaker and stirring at 80 rpm for 6 hours.
[0151] Additionally, the step of preparing the secondary seed may further include a drying step for drying the mixed secondary weighed material. Here, the drying step may be performed by placing the mixture in a dish and drying it at a temperature of 100°C for 3 hours.
[0152] For example, the step of performing the topochemical reaction can be carried out by placing the dried secondary seed material in a crucible at 975°C for 6 hours. By performing the topochemical reaction, the bismuth (Bi) contained in the primary seed can be exchanged for sodium (Na). The topochemical reaction will be described in detail later with reference to FIG. 21.
[0153] Here, the step of carrying out the topochemical reaction can be called secondary calcination.
[0154] The step of preparing the secondary seed (S24) may further include a step of washing the secondary seed after the topochemical reaction is completed.
[0155] For example, the step of washing the secondary seed can be performed by washing it 5 to 10 times with water at 80°C or higher to remove sodium chloride (NaCl) adhering to the NN seed, and then filtering it.
[0156] In addition, to remove bismuth (Bi) remaining in the NN seeds even after washing and filtering, acid treatment with nitric acid can be performed several times followed by neutralization washing with water. For example, nitric acid can be poured into a beaker, the NN seeds can be added and shaken every 10 minutes, and this can be repeated for 1 to 2 hours.
[0157] Figure 21 illustrates the crystal changes occurring during the step of preparing the secondary seed. Bi2O2[(Bi0.5 Na 3.5 )Nb5O 16 The crystal structure having the composition of ] illustrates the primary seed, and can be referred to as the BNN seed below. Next, the crystal structure having the composition of NaNbO3 shown on the right illustrates the secondary seed, and can be referred to as the NN seed below.
[0158] Referring to Fig. 21, Bi2O2[(Bi 0.5 Na 0.5 )Nb5O 16 The crystal structure of the primary seed having the composition of ] is, from the top, NbO6 octahedrons and layers of sodium (Na) and bismuth (Bi) interspersed between the NbO6 octahedrons, (Bi2O2) 2+ Layer, pseudo-perovskite layer, (Bi2O2) 2+ It may be a structure in which layers of sodium (Na) and bismuth (Bi) are mixed between NbO6 octahedrons and repeating layers between the NbO6 octahedrons. Next, the crystal structure of a secondary seed having a NaNbO3 composition may have a structure in which sodium (Na) surrounds an NbO6 octahedron at the center.
[0159] In the step (S24) of preparing the secondary seed of FIG. 21, the primary seed can be converted into a secondary seed by a topochemical reaction. Here, topochemical refers to a chemical reaction in which the orientation of the parent crystal and the crystal orientation of the product have different orientational relationships, while the shape of the crystal grain is preserved.
[0160] Therefore, as illustrated in FIG. 21, during the process in which the Bi element of the primary seed is substituted with the Na element, a layer containing sodium (Na) and bismuth (Bi) is formed between the NbO6 octahedrons (Bi2O2). 2Both the + layer and the pseudo-perovskite layer can be converted into a single structure having a NaNbO3 composition.
[0161] FIG. 22 is a perspective view of a display device according to an embodiment of the present specification, and FIG. 23 is a cross-sectional view taken along the cutting line I-I' of FIG. 22.
[0162] Referring to FIGS. 22 and 23, an apparatus according to an embodiment of the present specification may include a vibrating member (100) that displays an image and a piezoelectric element (200) that vibrates the vibrating member (100) from the rear (or back) side of the vibrating member (100).
[0163] The device according to the embodiments of the present specification may include a vibrating member and a piezoelectric element (200) disposed on the back (or rear) surface of the vibrating member. For example, the vibrating member may output sound according to the vibration of the vibrating device (200). For example, the vibrating member may be a vibrating object, a display panel, a diaphragm, or a front member, but is not limited thereto.
[0164] For example, a vibrating member or vibrating object may include one or more of a display panel having pixels for displaying an image, a screen panel on which an image is projected from a display device, a lighting panel, a signage panel, interior materials of a means of transport, windows of a means of transport, exterior materials of a means of transport, ceiling materials of a building, interior materials of a building, windows of a building, interior materials of an aircraft, windows of an aircraft, wood, plastic, glass, metal, cloth, fiber, paper, rubber, leather, and mirror.
[0165] In the following description, the vibration member (100) is described as being a display panel (100).
[0166] The display panel (100) can display an image, for example, an electronic image, a digital image, a still image, or a video image. For example, the display panel (100) can display an image by outputting light. The display panel (100) can be any type of display panel or a curved display panel, such as a liquid crystal display panel, an organic light-emitting display panel, a quantum dot light-emitting display panel, a micro light-emitting diode display panel, and an electrophoretic display panel. The display panel (100) can be a flexible display panel. For example, the display panel (100) can be a flexible light-emitting display panel, a flexible electrophoretic display panel, a flexible electronic wet display panel, a flexible micro light-emitting diode display panel, or a flexible quantum dot light-emitting display panel, but is not limited thereto.
[0167] A display panel (100) according to an embodiment of the present specification may include a display area (AA) that displays an image according to the driving of a plurality of pixels. Additionally, the display panel (100) may further include a non-display area (IA) surrounding the display area (AA), but is not necessarily limited thereto.
[0168] The piezoelectric element (200) can provide acoustic and / or haptic feedback to the user based on the vibration of the display panel (100) by vibrating the display panel (100) from the rear of the display panel (100). The piezoelectric element (200) can be implemented on the rear of the display panel (100) so as to directly vibrate the display panel (100).
[0169] In an embodiment of the present specification, the piezoelectric element (200) can vibrate according to a vibration driving signal synchronized with an image displayed on the display panel (100) to vibrate the display panel (100). In another embodiment, the piezoelectric element (200) can vibrate according to a haptic feedback signal (or tactile feedback signal) synchronized with a user touch on a touch panel (or touch sensor layer) placed on or embedded in the display panel (100) to vibrate the display panel (100). Accordingly, the display panel (100) can vibrate according to the vibration of the piezoelectric element (200) to provide at least one of acoustic and haptic feedback to the user (or viewer).
[0170] The piezoelectric element (200) according to the embodiment of the present specification may be implemented with a size corresponding to the display area (AA) of the display panel (100). The size of the piezoelectric element (200) may be 0.9 to 1.1 times the size of the display area (AA), but is not limited thereto. For example, the size of the piezoelectric element (200) may be the same as or smaller than the size of the display area (AA). For example, the size of the piezoelectric element (200) may be the same as or nearly the same as the size of the display area (AA) of the display panel (100), so that most of the area of the display panel (100) can be covered, and since the vibration generated by the piezoelectric element (200) can vibrate the entire display panel (100), the sense of acoustic localization is high and user satisfaction can be improved. In addition, the contact area (or panel coverage) between the display panel (100) and the piezoelectric element (200) can be increased, thereby increasing the vibration area of the display panel (100), so that the mid-low frequency sound generated by the vibration of the display panel (100) can be improved. Furthermore, since the piezoelectric element (200) applied to the large display device can vibrate the entire large (or large-area) display panel (100), the sense of sound localization due to the vibration of the display panel (100) is further enhanced, thereby enabling the realization of an enhanced sound effect. Accordingly, the piezoelectric element (200) according to the embodiment of the present specification is placed on the rear of the display panel (100) and can sufficiently vibrate the display panel (100) in the up-down (or front-back) direction, so that sound can be output to the front of the device or display device.
[0171] The piezoelectric element (200) according to the embodiment of the present specification may be implemented in the form of a film. Since the piezoelectric element (200) is implemented in the form of a film, it may have a thinner thickness than the display panel (100), so the increase in thickness of the display device due to the placement of the piezoelectric element (200) can be minimized. For example, the piezoelectric element (200) may be described as an acoustic generating module, an acoustic generating device, a film actuator, a film-type piezoelectric composite actuator, a film speaker, a film-type piezoelectric speaker, or a film-type piezoelectric composite speaker, but is not limited to these terms. In another embodiment, the piezoelectric element (200) may not be placed on the rear surface of the display panel (100) but may be applied to a vibration object other than the display panel. For example, the object of vibration may be a non-display panel, wood, metal, plastic, glass, cloth, paper, mirror, fiber, rubber, leather, interior material of a car, window of a car, interior ceiling of a building, window of a building, interior material of an aircraft, and window of an aircraft, but is not limited thereto. For example, the non-display panel may be a light-emitting diode lighting panel (or device), an organic light-emitting lighting panel (or device), or an inorganic light-emitting lighting panel (or device), but is not limited thereto. In this case, the object of vibration may be applied as a diaphragm, and the piezoelectric element (200) may vibrate the object of vibration to output sound.
[0172] The piezoelectric element (200) according to the embodiment of the present specification may further include a vibration structure (230) and a connecting member (210) disposed between the vibration structure (230) and the display panel (100).
[0173] According to an embodiment of the present specification, the connecting member (210) may include at least one substrate and may include an adhesive layer attached to one or both sides of the substrate, or may be composed of a single layer of adhesive.
[0174] For example, the connecting member (210) may include a foam pad, double-sided tape, or adhesive, but is not limited thereto. For example, the adhesive layer of the connecting member (210) may include epoxy, acrylic, silicone, or urethane, but is not limited thereto.
[0175] The device according to the embodiment of the present specification may further include a support member (300) disposed on the rear surface of the display panel (100).
[0176] The support member (300) can cover the rear surface of the display panel (100). For example, the support member (300) can cover the entire rear surface of the display panel (100) with a gap space (GS) in between. For example, the support member (300) may include at least one material among glass, metal, and plastic. For example, the support member (300) may be a rear structure or a set structure. For example, the support member (300) may be expressed by other terms such as a cover bottom, plate bottom, back cover, base frame, metal frame, metal chassis, chassis base, or m-chassis. Accordingly, the support member (300) can be implemented as any form of frame or plate-like structure placed on the rear surface of the display panel (100).
[0177] The device according to the embodiment of the present specification may further include a middle frame (400).
[0178] The middle frame (400) may be positioned between the rear edge of the display panel (100) and the front edge portion of the support member (300). The middle frame (400) may support one or more of the edge portions of the display panel (100) and the support member (300), respectively, and may surround one or more of the sides of the display panel (100) and the support member (300). The middle frame (400) may form a gap space (GS) between the display panel (100) and the support member (300). The middle frame (400) may be described as a middle cabinet, a middle cover, or a middle chassis, but is not limited to these terms.
[0179] A middle frame (400) according to an embodiment of the present specification may include a first support portion (410) and a second support portion (430).
[0180] The first support portion (410) may form a gap space (GS) between the display panel (100) and the support member (300) by being positioned between the rear edge of the display panel (100) and the front edge of the support member (300). The front of the first support portion (410) may be combined or connected to the rear edge portion of the display panel (100) via the first frame connecting member (401). The rear of the first support portion (410) may be combined or connected to the front edge portion of the support member (300) via the second frame connecting member (403). For example, the first support portion (410) may include a single square frame structure or a frame structure having multiple divided bars.
[0181] The second support portion (430) may be coupled perpendicularly to the outer surface of the first support portion (410) so as to be parallel to the thickness direction (Z) of the device. The second support portion (430) may protect the outer surfaces of the display panel (100) and the support member (300) respectively by surrounding one or more of the outer surfaces of the display panel (100) and the support member (300). The first support portion (410) may protrude from the inner surface of the second support portion (430) toward the gap space (GS) between the display panel (100) and the support member (300).
[0182] FIG. 24 is a detailed drawing of the piezoelectric element of FIG. 23.
[0183] Referring to FIG. 24, a piezoelectric element (200) according to an embodiment of the present specification may include a vibration structure (230), and the vibration structure (230) may include a piezoelectric element layer (231), a first electrode portion (233) disposed on a first surface of the piezoelectric element layer (231), and a second electrode portion (235) disposed on a second surface opposite to the first surface.
[0184] The piezoelectric element layer (231) includes a first material layer (231a) and a second material layer (231b) surrounded by the first material layer (231a). According to an embodiment of the present specification, one first material layer (231a) and a second material layer (231b) can form a single grain having the same crystal direction, and a grain boundary (GB) can be formed in the portion in contact with another first material layer (231a) and a second material layer (231b) forming an adjacent grain.
[0185] According to an embodiment of the present specification, the first material layer (231a) has grains grown based on the crystal direction of the second material layer (231b), so that a plurality of first material layers (231a) may have the same crystal direction, for example, (001) crystal direction.
[0186] The first electrode part (233) and the second electrode part (235) may use metal electrodes, for example, silver electrodes may be used, but are not limited thereto.
[0187] Additionally, although the vibration structure (230) in FIG. 19 is shown as a single layer, it may be configured to be additionally stacked according to the required performance value of the piezoelectric element. The piezoelectric element according to the embodiment of the present specification may be applied to a vibration device placed in the device. The device according to the embodiments of the present specification may be applied to mobile devices, video phones, smart watches, watch phones, wearable apparatuses, foldable apparatuses, rollable apparatuses, bendable apparatuses, flexible apparatuses, curved apparatuses, sliding apparatuses, variable apparatuses, electronic notebooks, e-books, PMPs (portable multimedia players), PDAs (personal digital assistants), MP3 players, mobile medical devices, desktop PCs, laptop PCs, netbook computers, workstations, navigation systems, vehicle navigation systems, vehicle display devices, vehicle devices, theater devices, theater display devices, televisions, wallpaper devices, signage devices, game devices, laptops, monitors, cameras, camcorders, and home appliances, etc. In addition, the vibration device of this specification may be applied to an organic light-emitting lighting device or an inorganic light-emitting lighting device. When the vibration device is applied to a lighting device, it may function as a light and a speaker. In addition, when the vibration device of this specification is applied to a mobile device, etc., it may be one or more of a speaker, a receiver, and a haptic device, but is not limited thereto.
[0188] The piezoelectric material composition according to the present specification can be represented by Chemical Formula 1.
[0189] [Chemical Formula 1]
[0190] 0.96(Na a K 1-a )(Nb b (T 1-b ))O3- (0.04-x)MZrO3- x(Bi c Ag 1-c )ZrO3(T=Sb, Ta), (M=Sr, Ba, Ca) + d mol% NaNbO3
[0191] (As stated above, a is 0.4 ≤ a ≤ 0.6, b is 0.90 ≤ b ≤ 0.98, c is 0.4 ≤ c ≤ 0.6, x is 0 ≤ x ≤ 0.04, and d is 0 ≤ d ≤ 5.0).
[0192] According to some embodiments of the present specification, a piezoelectric material composition may comprise a first material; and a second material surrounded by the first material.
[0193] According to some embodiments of the present specification, the aspect ratio of the first material may be 5 to 20.
[0194] According to some embodiments of the present specification, the second material may be NaNbO3.
[0195] According to some embodiments of the present specification, the second material may be added in an amount of 0 to 5 mol% to the piezoelectric material composition of Formula 1.
[0196] According to some embodiments of the present specification, the first material comprises a plurality of crystal grains that are crystally oriented in a single direction (001), a second material is disposed inside the plurality of crystal grains, and the plurality of crystal grains can grow by reacting with the second material.
[0197] According to some embodiments of the present specification, the Rogering factor of the piezoelectric material composition may be 94% or more.
[0198] According to some embodiments of the present specification, the piezoelectric material composition may have at least two phases coexisting at room temperature among tetragonal (T), orthorhombic (O), and rhombohedral (R).
[0199] According to some embodiments of the present specification, the piezoelectric material composition may include nano domains.
[0200] According to some embodiments of the present specification, the piezoelectric material composition may include polar nano regions (PNRs).
[0201] A method for manufacturing a piezoelectric material composition according to the present specification comprises the steps of: weighing a matrix material and a seed material; mixing the matrix material and the seed material to prepare a slurry; molding the slurry to prepare a molded body; and sintering the molded body to prepare a sintered body, wherein the weighed matrix material and seed material may be represented by Chemical Formula 1.
[0202] [Chemical Formula 1]
[0203] 0.96(Na a K 1-a )(Nb b (T 1-b ))O3- (0.04-x)MZrO3- x(Bi c Ag 1-c )ZrO3(T=Sb, Ta), (M=Sr, Ba, Ca) + d mol% NaNbO3
[0204] (As stated above, a is 0.4 ≤ a ≤ 0.6, b is 0.90 ≤ b ≤ 0.98, c is 0.4 ≤ c ≤ 0.6, x is 0 ≤ x ≤ 0.04, and d is 0 ≤ d ≤ 5.0).
[0205] According to some embodiments of the present specification, the matrix material may be represented by Chemical Formula 2.
[0206] [Chemical Formula 2]
[0207] 0.96(Na a K 1-a )(Nb b (T 1-b))O3- (0.04-x)MZrO3- x(Bi c Ag 1-c )ZrO3(T=Sb, Ta), (M=Sr, Ba, Ca)
[0208] (As stated above, a is 0.4 ≤ a ≤ 0.6, b is 0.90 ≤ b ≤ 0.98, c is 0.4 ≤ c ≤ 0.6, and x is 0 ≤ x ≤ 0.04)
[0209] According to some embodiments of the present specification, the seed material may be a NaNbO3 single crystal.
[0210] According to some embodiments of the present specification, the seed material may be added in an amount of 0 to 5 mol% to the piezoelectric material composition of Formula 1.
[0211] According to some embodiments of the present specification, the step of preparing a sintered body is 1070 o C to 1110 o It can be maintained in C for 3 to 6 hours.
[0212] According to some embodiments of the present specification, prior to performing the step of weighing the matrix material and the seed material, the matrix material may be prepared by the step of weighing raw materials to manufacture the matrix material; the step of mixing and synthesizing the weighed raw materials; and the step of grinding the synthesized matrix material.
[0213] According to some embodiments of the present specification, prior to performing weighing a matrix material and a seed material, the seed material comprises the steps of: first weighing the seed material; preparing a primary seed; secondly weighing including the primary seed; and preparing a secondary seed, wherein the primary seed is (Bi 2.5 Na 3.5 )Nb5O 16 And, the secondary seed can be NaNbO3.
[0214] According to some embodiments of the present specification, the step of preparing a secondary seed can be carried out through a topochemical reaction of a weighed mixture of a primary seed, sodium carbonate (Na2CO3), and sodium chloride (NaCl).
[0215] According to some embodiments of the present specification, in the step of weighing the matrix material and the seed material, the matrix material comprises iron oxide (Fe2O3), and 5 mol% of NaNbO3 seed may be added to the piezoelectric material composition.
[0216] A piezoelectric element according to the present specification comprises: a piezoelectric element layer comprising a first material and a second material surrounded by the first material; a first electrode portion disposed on a first surface of the piezoelectric element layer; and a second electrode portion disposed on a second surface opposite to the first surface, and the piezoelectric element layer may be represented by Formula 1.
[0217] [Chemical Formula 1]
[0218] 0.96(Na a K 1-a )(Nb b (T 1-b ))O3- (0.04-x)MZrO3- x(Bi c Ag 1-c )ZrO3(T=Sb, Ta), (M=Sr, Ba, Ca) + d mol% NaNbO3
[0219] (As stated above, a is 0.4 ≤ a ≤ 0.6, b is 0.90 ≤ b ≤ 0.98, c is 0.4 ≤ c ≤ 0.6, x is 0 ≤ x ≤ 0.04, and d is 0 ≤ d ≤ 5.0).
[0220] According to some embodiments of the present specification, the second material may be NaNbO3.
[0221] According to some embodiments of the present specification, the second material may be added in an amount of 0 to 5 mol% to the piezoelectric material composition of Formula 1.
[0222] According to some embodiments of the present specification, the first material comprises a plurality of crystal grains that are crystally oriented in a single direction (001), a second material is disposed inside the plurality of crystal grains, and the plurality of crystal grains can grow by reacting with the second material.
[0223] According to some embodiments of the present specification, the Rogering factor of the piezoelectric material composition may be 94% or more.
[0224] A display device according to the present specification may include a vibrating member; and a piezoelectric element disposed on the rear surface of the vibrating member.
[0225] Although the embodiments of this specification have been described in more detail with reference to the attached drawings, this specification is not necessarily limited to these embodiments and may be modified in various ways within the scope of the technical spirit of this specification. Accordingly, the embodiments disclosed in this specification are intended to explain, not limit, the technical spirit of this specification, and the scope of the technical spirit of this specification is not limited by these embodiments. Therefore, the embodiments described above should be understood as illustrative in all respects and not restrictive. The scope of protection of this specification shall be interpreted by the claims, and all technical spirits within an equivalent scope shall be interpreted as being included within the scope of rights of this specification. Explanation of the symbols
[0226] 10: Piezoelectric material composition 11: First material 12: Second material 13: Electrode part 100: Display panel 200: Piezoelectric element 210: Connecting member 230: Vibrating part 231: Piezoelectric element layer 231a: First material layer 231b: Second material layer 233: First electrode part 235: Second electrode part 300: Support member 400: Middle frame
Claims
Claim 1 In a piezoelectric material composition represented by Chemical Formula 1, [Chemical Formula 1]0.96(Na a K 1-a )(Nb b (T 1-b ))O3- (0.04-x)MZrO3- x(Bi c Ag 1-c )ZrO3+ d mol% NaNbO3(wherein a is 0.4 ≤ a ≤ 0.6, b is 0.90 ≤ b ≤ 0.98, c is 0.4 ≤ c ≤ 0.6, x is 0 ≤ x ≤ 0.04, d is 0 ≤ d ≤ 5.0, T is Sb or Ta, and M is Sr, Ba or Ca), the piezoelectric material composition comprises a first material; and a second material surrounded by the first material, wherein the first material is represented by Chemical Formula 2, [Chemical Formula 2]0.96(Na a K 1-a )(Nb b (T 1-b ))O3- (0.04-x)MZrO3- x(Bi c Ag 1-c )ZrO3 (wherein a is 0.4 ≤ a ≤ 0.6, b is 0.90 ≤ b ≤ 0.98, c is 0.4 ≤ c ≤ 0.6, x is 0 ≤ x ≤ 0.04, T is Sb or Ta, and M is Sr, Ba or Ca), the second material is NaNbO3, a piezoelectric material composition. Claim 2 delete Claim 3 A piezoelectric material composition according to claim 1, wherein the aspect ratio of the first material is 5 to 20. Claim 4 delete Claim 5 The piezoelectric material composition according to claim 1, wherein the second material is added in an amount of 0 to 5 mol% to the piezoelectric material composition of formula 1. Claim 6 A piezoelectric material composition according to claim 1, wherein the first material comprises (001) a plurality of crystal grains crystally oriented in a single direction, the second material is disposed inside the plurality of crystal grains, and the plurality of crystal grains are grown by reacting with the second material. Claim 7 A piezoelectric material composition according to claim 1, wherein the Rogering factor of the piezoelectric material composition is 94% or more. Claim 8 In claim 1, the piezoelectric material composition is a piezoelectric material composition in which at least two phases among tetragonal (T), orthorhombic (O), and rhombohedral (R) coexist at room temperature. Claim 9 In claim 1, the piezoelectric material composition comprises a nano domain. Claim 10 In claim 1, the piezoelectric material composition comprises a polar nano region (PNR). Claim 11 The method comprises the steps of: weighing a matrix material and a seed material; mixing the matrix material and the seed material to prepare a slurry; molding the slurry to prepare a molded body; and sintering the molded body to prepare a sintered body, wherein the weighed matrix material and seed material are a piezoelectric material composition represented by Chemical Formula 1, and [Chemical Formula 1]0.96(Na a K 1-a )(Nb b (T 1-b ))O3- (0.04-x)MZrO3- x(Bi c Ag 1-c )ZrO3+ d mol% NaNbO3(wherein a is 0.4 ≤ a ≤ 0.6, b is 0.90 ≤ b ≤ 0.98, c is 0.4 ≤ c ≤ 0.6, x is 0 ≤ x ≤ 0.04, d is 0 ≤ d ≤ 5.0, T is Sb or Ta, and M is Sr, Ba or Ca), the above matrix material is represented by Chemical Formula 2, and [Chemical Formula 2]0.96(Na a K 1-a )(Nb b (T 1-b ))O3- (0.04-x)MZrO3- x(Bi c Ag 1-c A method for preparing a piezoelectric material composition, wherein the seed material is NaNbO3 (wherein a is 0.4 ≤ a ≤ 0.6, b is 0.90 ≤ b ≤ 0.98, c is 0.4 ≤ c ≤ 0.6, x is 0 ≤ x ≤ 0.04, T is Sb or Ta, and M is Sr, Ba or Ca), and the seed material is NaNbO3. Claim 12 delete Claim 13 A method for manufacturing a piezoelectric material composition according to claim 11, wherein the seed material is a single crystal. Claim 14 A method for preparing a piezoelectric material composition according to claim 11, wherein the seed material is added in an amount of 0 to 5 mol% to the piezoelectric material composition of Formula 1. Claim 15 In claim 11, the step of preparing the sintered body is 1070 o C to 1110 o A method for manufacturing a piezoelectric material composition maintained at C for 3 to 6 hours. Claim 16 A method for manufacturing a piezoelectric material composition according to claim 11, wherein, prior to performing the step of weighing the matrix material and the seed material, the matrix material is prepared by the step of weighing raw materials to manufacture the matrix material; the step of mixing and synthesizing the weighed raw materials; and the step of grinding the synthesized matrix material. Claim 17 In claim 11, prior to performing the weighing of the matrix material and the seed material, the seed material comprises the steps of: first weighing the seed material; preparing a first seed; second weighing including the first seed; and preparing a second seed, wherein the first seed is (Bi 2.5 Na 3.5 )Nb5O 16 A method for manufacturing a piezoelectric material composition, wherein the secondary seed is NaNbO3. Claim 18 A method for preparing a piezoelectric material composition according to claim 17, wherein the step of preparing the secondary seed is performed through a topochemical reaction of a mixture of the primary seed, sodium carbonate (Na2CO3), and sodium chloride (NaCl) that has been weighed. Claim 19 A method for manufacturing a piezoelectric material composition according to claim 11, wherein, in the step of weighing a matrix material and a seed material, the matrix material comprises iron oxide (Fe2O3), and 5 mol% of NaNbO3 seed is added to the piezoelectric material composition. Claim 20 A piezoelectric element layer comprising a first material and a second material surrounded by the first material; a first electrode portion disposed on a first surface of the piezoelectric element layer; and a second electrode portion disposed on a second surface opposite to the first surface, wherein the piezoelectric element layer is represented by Chemical Formula 1, [Chemical Formula 1]0.96(Na a K 1-a )(Nb b (T 1-b ))O3- (0.04-x)MZrO3- x(Bi c Ag 1-c )ZrO3+ d mol% NaNbO3(wherein a is 0.4 ≤ a ≤ 0.6, b is 0.90 ≤ b ≤ 0.98, c is 0.4 ≤ c ≤ 0.6, x is 0 ≤ x ≤ 0.04, d is 0 ≤ d ≤ 5.0, T is Sb or Ta, and M is Sr, Ba or Ca), the first substance is represented by Chemical Formula 2, and [Chemical Formula 2]0.96(Na a K 1-a )(Nb b (T 1-b ))O3- (0.04-x)MZrO3- x(Bi c Ag 1-c )ZrO3 (wherein a is 0.4 ≤ a ≤ 0.6, b is 0.90 ≤ b ≤ 0.98, c is 0.4 ≤ c ≤ 0.6, x is 0 ≤ x ≤ 0.04, T is Sb or Ta, and M is Sr, Ba or Ca), the second material is NaNbO3, a piezoelectric element. Claim 21 delete Claim 22 In claim 20, the piezoelectric element, wherein the second material is added in an amount of 0 to 5 mol% with respect to Formula 1. Claim 23 In claim 20, the first material comprises a plurality of crystal grains that are crystally oriented in a single direction (001), the second material is disposed inside the plurality of crystal grains, and the plurality of crystal grains are grown by reacting with the second material, a piezoelectric element. Claim 24 A method for manufacturing a piezoelectric material composition according to claim 19, wherein the Rogering factor of the piezoelectric material composition is 94% or more. Claim 25 A display device comprising: a vibrating member; and a piezoelectric element disposed on the rear surface of the vibrating member and according to any one of claims 20, 22 and 23.
Citation Information
Patent Citations
Piezoelectric ceramic, its producing method and piezoelectric element using the piezoelectric ceramic
JP2009242166A
Method for manufacturing rectangular parallelepiped single crystal, rectangular parallelepiped single crystal, ceramics, piezoelectric element and electronic apparatus
JP2016172686A